2016
DOI: 10.3899/jrheum.150857
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept Increases Bone Mineral Density in Ankylosing Spondylitis, but Does Not Prevent Vertebral Fractures: Results of a Prospective Observational Cohort Study

Abstract: This prospective longitudinal observational cohort study showed that after 2 years of ETN, BMD of the hip and spine increased significantly, but the number of patients with VFx and the severity of VFx increased as well. Besides that, radiological progression, including the thoracic spine, increased significantly. Thus, the favorable bone-preserving effect is accompanied by unfavorable outcomes on VFx and radiological damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
3
14
0
1
Order By: Relevance
“…Cytokines released from Th1 and Th2 cells can antagonize each other and inhibit the Th reactions and the release of related factors. The Th1 cytokine IFN-g can antagonize the secretion of Th2 cytokines IL-4 and IL-10, which further inhibits the Th2 reaction (van der Weijden et al, 2016). This study revealed significantly lower levels of serum IL-4 and IL-10 in patients with active AS, who also had higher levels of TNF-a and IFN-g, thereby indicating that imbalance in Th1/Th2 cell numbers might be involved in the pathogenesis of AS.…”
Section: Discussionmentioning
confidence: 59%
“…Cytokines released from Th1 and Th2 cells can antagonize each other and inhibit the Th reactions and the release of related factors. The Th1 cytokine IFN-g can antagonize the secretion of Th2 cytokines IL-4 and IL-10, which further inhibits the Th2 reaction (van der Weijden et al, 2016). This study revealed significantly lower levels of serum IL-4 and IL-10 in patients with active AS, who also had higher levels of TNF-a and IFN-g, thereby indicating that imbalance in Th1/Th2 cell numbers might be involved in the pathogenesis of AS.…”
Section: Discussionmentioning
confidence: 59%
“…TNFi treatment also shows a positive effect with respect to BMD, both of the hip and lumbar spine . In half of these studies bone formation was confirmed; in the other half no significant changes were found between the patient group and the control group . It should be noted, however, that the effect of TNFi on BMD has only been measured with a maximum follow‐up duration of 3 years.…”
Section: Introductionmentioning
confidence: 95%
“…So far, only two studies have examined the long‐term effect of TNFis on the incidence of VFxs. Van der Weijden and colleagues and Maas et al studied the effect of TNFi treatment on the incidence of VFxs with a subsequent follow‐up duration of 2 and 4 years. From these studies, it can be concluded that despite the treatment with TNFis, the prevalence of VFxs still increased.…”
Section: Introductionmentioning
confidence: 99%
“…Mean BMD change was 5.8% at the spine and 2.3% at the hip in comparison to baseline [41]. Similarly, in a prospective observational study of 49 patients with AS by van der Weijden et al, treatment with etanercept was associated with a significant increase in BMD at the spine and hip at two years (p<0.0001 and p=0.014, respectively) [42]. Despite therapy with etanercept, the number of vertebral fractures more than doubled in two years and fracture severity increased.…”
Section: Treatmentmentioning
confidence: 98%